PENERAPAN BEKAM BASAH TERHADAP PENURUNAN NYERI DENGAN NEUROPATI KOMPRESI DIKLINIK ZEIN HOLISTIC - Siti Hafifah Rusli Sinata; Samsualam; Eliati Paturungi; Sunarti (Jurnal Kesehatan, 2025)
Lower back pain is a common musculoskeletal complaint and can be caused by compression neuropathy due to pressure on peripheral nerves or spinal nerve roots. Wet cupping therapy is known as a complementary method that has the potential to reduce pain intensity by increasing blood circulation, removing metabolic waste products, and stimulating endorphin release. This study aims to determine the application of wet cupping therapy to reduce low back pain in patients with compression neuropathy at the Zein Holistic Therapy Clinic in Makassar City. This study used a case study method on a 40-year-old female patient with complaints of low back pain radiating to the legs with an initial pain scale of 5 (moderate) as measured using the Numerical Rating Scale (NRS). The intervention was carried out in the form of wet cupping therapy according to standard operating procedures for nursing, followed by post-intervention pain measurements. The results showed a decrease in the pain scale from 5 to 2 after wet cupping therapy. The conclusion of this study is that wet cupping therapy is effective in reducing low back pain in patients with compression neuropathy, so it can be recommended as a non-pharmacological intervention in evidence-based nursing care.